Rancang Bangun Sistem Informasi Penjualan Buket Bunga Kain Flanel Florist Menggunakan Metode Waterfall - Yamin Nuryamin; Sandra Dewi Saraswati (JURIKOM (Jurnal Riset Komputer), 2018)
Along with the development of technological advances today is very useful for us in searching for an information that is so fast, precise and accurate in everyday life, especially in helping solve our work, with the system has been computerized is expected to help all the hard work done easy to do in order to get better results than before. Now the bouquet of flowers began to boom starting from the original or not original flowers, from fabric, paper or plastic and of course in a variety of shapes and sizes according to consumer demand. Based on the above facts, the authors make a sales bouquet of flowers that utilize the internet is very influential in promoting. As a tool in data processing can facilitate the processing of transaction data in a way that is easier and efficient and data storage can save space, facilitate the search data at the time of repair and recap data.In testing this information system-based website application using the waterfall software design method, because it is easier to implement and implement.